2015
DOI: 10.3402/gha.v8.28045
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the perceptions and experiences of community health workers using role identity theory

Abstract: BackgroundCommunity health workers (CHWs) are an integral resource in many health systems, particularly in resource-poor settings. Their identities – ‘who’ they are – play an important role in their hiring, training, and retention. We explore the perceptions, experiences, and identities of CHWs as they adopt a CHW role in rural South Africa, using ‘role identity theory’.DesignFrom April to December 2010, we conducted 18 semi-structured interviews with CHWs volunteering in non-governmental home-based care (HBC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 33 publications
5
70
0
Order By: Relevance
“…The role of the CHWs within the outreach teams is mainly to strengthen the interface between the households and health facility services [12,13]. The CHWs provide various services, which include linking communities to the healthcare system, preventative care and keeping track with disease outbreak [21], as well as offering community-based healthcare and social support to complement rather than substitute the more specialised services of the healthcare system [13]. In a study conducted in rural South Africa, it was reported that the CHWs negotiated and established a personalised client-centred package of care, and that they continually assessed and adapted the package of services for each client and household as circumstances evolved [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the CHWs within the outreach teams is mainly to strengthen the interface between the households and health facility services [12,13]. The CHWs provide various services, which include linking communities to the healthcare system, preventative care and keeping track with disease outbreak [21], as well as offering community-based healthcare and social support to complement rather than substitute the more specialised services of the healthcare system [13]. In a study conducted in rural South Africa, it was reported that the CHWs negotiated and established a personalised client-centred package of care, and that they continually assessed and adapted the package of services for each client and household as circumstances evolved [12].…”
Section: Introductionmentioning
confidence: 99%
“…CHWs repeatedly visits clients, personally attend to them, collect their medicines and advocate for them with either their families or health providers in cases of access barriers [13]. The WHO indicate that CHWs are essential in PHC as they have been shown to assist in improving health outcomes in communities [12,21]. …”
Section: Introductionmentioning
confidence: 99%
“…While the response rate was lower in 2014 (30%) than in 2010 (50%), the demographic characteristics of the respondents were similar in the two surveys (Table lution in Minnesota. 5 This theory helped explain why the faculty members could remain true to their teaching role while beginning the process of understanding the new profession. Conceptually, role identity is the process by which individuals give meaning to themselves in relation to a specific role; it explains how roles develop in societies and how people represent who they are in various contexts, including their working environment.…”
Section: Resultsmentioning
confidence: 99%
“…First, CHWs and PLH in the FGD were all women. The gender composition of CHWs is representative of CHWs’ gender in general (Kane et al, 2016; Mlotshwa et al, 2015). The gender composition of PLH does not reflect the gender composition of the HIV epidemic and highlights difficulties in engaging and retaining South African men in care (Geng et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We examine perceptions towards mHealth, biometric identification and essential features in future mHealth systems. We build on prior qualitative work in South Africa that examined perceptions of Mxit (a social media network) users towards the proposed National Health Insurance plan (Weimann & Stuttaford, 2014), perceptions of young people towards youth-oriented health services (Schriver, Meagley, Norris, Geary & Stein, 2014), CHW roles (Druetz, Kadio, Haddad, Kouanda & Ridde, 2015; Kane et al, 2016; Mlotshwa, Harris, Schneider & Moshabela, 2015), perceptions of program managers and researchers towards mHealth capabilities and CHWs (Leon & Schneider, 2012), and perceptions of bank employees (Pooe & Labuschagne, 2011) and the general population (Riley, Buckner, Johnson & Benyon, 2009) towards biometric technology used for identification.…”
Section: Introductionmentioning
confidence: 99%